Pengembangan Media Pembelajaran Interaktif Berbasis Canva pada Materi Unggah-Ungguh Basa untuk SMP Kelas VII di SMPI Al-Fattahiyyah - Nur Dwi Istiqomah; Fahrur Rozi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Indonesia’s education system faces various challenges, including low learning quality and high dropout rates, particularly in Tulungagung Regency. At SMP Islam Al-Fattahiyyah, students’ achievement in Javanese language—especially in the unggah-ungguh basa material—remains low, and many students are still unable to use the krama language properly. Therefore, engaging and interactive learning media are needed. This study aims to develop Canva-based interactive learning media for the unggah-ungguh basa material and to determine its feasibility. The research employed a Research and Development (R&D) method using the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). The material was adapted from textbooks and teaching modules for grade VII. The research subjects included two media expert lecturers, one Javanese language teacher as a material expert, and grade VII students. The instruments used were media evaluation sheets, material evaluation sheets, and student response questionnaires. The results showed that the media was considered highly feasible, with a score of 96% from media experts, 95% from the material expert, 91% from small group testing, and 90% from field testing, resulting in an average of 93%. Therefore, the Canva-based interactive learning media is feasible to be used in teaching unggah-ungguh basa to grade VII students at SMP Islam Al-Fattahiyyah.